2013
DOI: 10.1371/journal.pone.0061608
|View full text |Cite|
|
Sign up to set email alerts
|

Higher Prevalence and Abundance of Bdellovibrio bacteriovorus in the Human Gut of Healthy Subjects

Abstract: IntroductionMembers of the human intestinal microbiota are key players in maintaining human health. Alterations in the composition of gut microbial community (dysbiosis) have been linked with important human diseases. Understanding the underlying processes that control community structure, including the bacterial interactions within the microbiota itself, is essential. Bdellovibrio bacteriovorus is a gram-negative bacterium that preys other gram-negative species for survival, acting as a population-balancer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 51 publications
2
100
0
1
Order By: Relevance
“…In this test, 20 marine bacteria which were susceptible to BDHSH06 (21) 33) were used to establish marine microcosms. The strains were identified by both analysis with an API 20E system and 16S rRNA gene sequencing (24).…”
Section: Figmentioning
confidence: 99%
“…In this test, 20 marine bacteria which were susceptible to BDHSH06 (21) 33) were used to establish marine microcosms. The strains were identified by both analysis with an API 20E system and 16S rRNA gene sequencing (24).…”
Section: Figmentioning
confidence: 99%
“…Then, it occupies the periplasmic space and undergoes growth phase which culminates in prey killing and release of progeny (4). B. bacteriovorus is ubiquitous both in aquatic and terrestrial habitats and has recently been discovered in the human gut, where it is alleged to act as a "probiotic" (5,6). Previous research has demonstrated that B. bacteriovorus has the potential to prey upon several human pathogens which grow in planktonic cultures or in biofilm (7).…”
Section: Introductionmentioning
confidence: 99%
“…Double-layered agar plating and PFU enumeration are widely used to detect and quantify predator biomass and to investigate predator host specificity (6). Additional methods utilize PCR and real-time quantitative PCR to determine the presence and bioload of predatory bacteria (9)(10)(11). Labeled oligonucleotide probes that target Bdellovibrio 16S rRNA were also used to visualize the predator by use of in situ fluorescence hybridization (12).…”
mentioning
confidence: 99%